The practice of English as a medium of instruction in an Indonesian higher education: Learners’ voices - Endrayanto, Nanang (Department of Language and Literature, Faculty of Cultural Studies, Universitas Brawijaya, 2021)
This study investigates teachers and students’ perceptions toward English instruction for international class program in Study Program of English, Faculty of Cultural Studies, Universitas Brawijaya in Indonesia. This study examines two issues: (1) students’ perception about the international class program and (2) students’ perception about English as a medium of instruction in the international program (bilingual or monolingual approach). This study employs quantitative method; Likert-scale survey with 34 university learners at undergraduate program participating in this study. The results revealed that learners were highly satisfied with the program and expecting more of monolingual approach than bilingual approach in the L2 classroom. It is recommended that the program have a minimum requirement of English proficiency to enroll in this program. It is expected that the results will provide a recommedation for policy maker to better generate an international class programs in the future.